Application of asphalt rubber cape seal as asphalt pavement surface course for rehabilitated trunk highway in east Gansu. Issue 1 (February 2021) - Han, L; Han, H; Guo, H; Zhu, J
Abstract: Although been frequently used as a preventative maintenance measure for asphalt pavements, the Cape seal process has not been widely adopted as a possible alternative for rehabilitated pavement. This research evaluated the feasibility of applying asphalt rubber Cape seal structure into the surface course of reconstructed highway in west China. The Cape seal is composed of 11-16 mm chips spread over asphalt rubber membrane sprayed in advance, by which followed a micro surfacing layer with SBR latex modified asphalt emulsion. Based on a test section in the Banxiao highway project, the construction of asphalt rubber Cape seal and micro-surfacing were investigated experimentally. In addition, to guide the engineers, major issues during construction of the Cape seal were discussed and corresponding countermeasures were suggested.